The EU origin of the Albanian legal regime on product liability - Nada Dollani (Europa-Kolleg Hamburg, Institute for European Integration, 2014)
The liability for defective products was for the first time introduced in 1994 by the new Civil Code. It widely reflects the liability regime provided by Directive 85/374 on product liability. In order to analyse the Albanian system on product liability as a special regime of extra-contractual liability, one should look at the Product Liability Directive, which is the source of inspiration for the Albanian regulation. Before the adoption of the Civil Code in 1994, no special regime of liability existed for the defective products due to the special features of economic and social order, based on centralised economy, on state property on the means of production, social and health insurance for all citizens and medical services provided by the state. The new regulation incorporated into the torts chapter of the Civil Code is not a full transposition of Product Liability Directive. However, it is considered as sufficient for the transposition duties of Albania under Stabilization and Association Agreement. When the Albanian legislator transposed a series of European directives on consumer protection, by adopting a separated legal act, Consumer Protection Law, it was assumed that this special area of tort did not need any amendment to bring it into consistency with the new regime of consumer protection and fully compatible with the Product Liability Directive. Considering the difficulties of law enforcement in South East European countries, this discussion paper aims at drawing a comparison between the European regime and the Albanian one so as to explain the specific features of the objective liability regime and identify the deficiencies in transposition, considering that the Product Liability Directive requires maximum harmonisation.
Keywords: 320; consumer expectation test; defective product; producer; risk development defence; strict liability